Cubosome based Nanocarriers for Drug Delivery: Recent Advances, Clinical Translation, and Future Perspectives - Ankita Gadhave; Sameer Shafi; Waghmare Pranita; Swami Shivlila; Damane Madhuri; Harshada Salunke (Asian Journal of Pharmaceutical Research and Development, 2026)
The bicontinuous cubic liquid crystalline phases are also being exploited as emerging lipid based nanocarriers, providing a novel three dimensional nanostructure with connected lipid bilayers and aqueous channels. This architecture allows the encapsulation of both hydrophilic, lipophilic and amphiphilic drugs with high loading, stability and controlled release properties. Cubosomes have been recently receiving a lot of attention in nanomedicine because of their bioavailability, drug stabilization, and therapeutic efficacy for various drug delivery platforms such as oral, topical, ocular, transdermal, pulmonary and parenteral delivery. With the development of formulation concepts (top down bottom up, hydrotrope dilution, solvent free and microfluidic technologies) their scalability and reproducibility have been enhanced. Furthermore, surface functionalization and stimuli responsive designs have facilitated targeted and theranostic uses in cancer therapy, neurological and ophthalmological diseases. These benefits are accompanied by manufacturing scale up, long term stability, regulatory issues and restricted clinical translation. Future studies will incorporate quality by design principles and advanced manufacturing techniques, which should help to expedite clinical development. Overall, cubosomes represent a versatile and promising platform for next generation drug delivery systems in precision nanomedicine.